Impact of preimplantation genetic testing for aneuploidies (PGT-A) on first trimester biochemical markers – PAPP-A (placenta-associated plasma protein) and free β-hCG (human chorionic gonadotropin). (12th December 2022) - Markova, D.; Kagan, O.; Hoopmann, M.; Abele, H.; Coughlan, C.; Abecia, E.; Fatemi, H. M.; Lawrenz, B.
Abstract: Objective: The objective of the study was to study the effect of preimplantation genetic testing for aneuploidies (PGT-A) performed at blastocyst stage on the levels of first trimester biomarkers. Methods: This is an observational, collaborative, retrospective study. Seven hundred and twenty-eight patients were included in the study. Patients were with singleton pregnancies resulting from either natural conception (NC), or assisted reproductive techniques (ARTs) with PGT-A and frozen embryo transfer (FET) (ART/PGT-A/FET) or after ART without PGT-A and fresh ET (ART/no PGT-A/fresh ET) or FET (ART/no PGT-A/FET), who had first trimester combined screening test between 11 and 14 gestational weeks. They were stratified into four groups: group A (ART/PGT-A/FET) – 143 patients; group B (ART/no PGT-A/FET) – 100 patients; group C (ART/no PGT-A/fresh ET) – 346 patients, and group D (NC) – 139 patients. Results: Statistically significant differences among the examined groups were observed for maternal age, BMI, ethnicity, and parity. The median placenta-associated plasma protein (PAPP-A) was lowest in the group with ART/PGT-A/FET and the highest result was obtained in the group with ART/no PGT-A/FET. Statistically significant difference in the median PAPP-A levels was identified among the examined groups ( p  = .0186). When a subgroup analysis was performed, a statistically significant difference was observed in the median PAPP-A between ART/PGT-A/FET group versus ART/no PGT-A/FET group ( p  = .01) and NC versus ART/no PGT-A/FET ( p  = .01). A similar trend toward statistical significance was noted when comparing NC versus ART/no PGT-A/fresh ET ( p  = .06). Multivariate analysis elucidated that when age is present in the model, the effect of any method of conception or testing for aneuploidy disappears. The other factors (BMI, ethnicity, and parity) do not influence the levels of PAPP-A. The lowest median free human chorionic gonadotropin (β-HCG) was recorded in the NC group and the highest result was identified in the group with IVF/PGT-A/FET. No statistically significant difference was observed in the median concentration levels of free β-hCG among the compared groups ( p  = .5789) and when subgroup analysis was performed ( p >.05). The normality of the distribution of variables was analyzed by the Kolmogorov–Smirnov test and the median PAPP-A and free βhCG concentration difference by the Wilcoxon rank-sum test with nonparametric ANOVA. Conclusions: Testing for aneuploidy (PGT-A) and the decision to transfer either fresh or cryopreserved embryos (ET) appear not to affect the levels of first trimester biochemical markers. The findings of the present study should be a baseline for future studies and could be used to improve the antenatal screening counseling for women with ART pregnancies and PGT-A.